Play To Learn: Exploring Gamification in an English Language E-Learning Platform - La Ode Rasmin; isma, Adi; Mega Januarti Putri, Andi; Sardi, Ahmed (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This study examined how gamification affected students' motivation, participation, teamwork, and learning outcomes in an English-language e-learning platform. Semi-structured interviews and structured observations were used in a qualitative case study. Sixty-two third-semester English education majors from Universitas Sulawesi Barat, Indonesia, participated in the study. They were specifically chosen from two classes that used an e-learning platform with gaming elements. The results showed that gamification components such as incentives, achievements, and challenges considerably enhanced learners' motivation, excitement, and active engagement in English learning activities. Furthermore, gamification fostered positive social interactions, including collaboration, idea-sharing, mutual support, and healthy competition among learners. The observation data corroborated these findings, demonstrating high engagement levels, effective utilization of gamification features, strong focus and persistence, and notable improvements in achieving English learning goals. The study concludes that gamification can produce interesting, fun, and productive learning environments that improve students' motivation, engagement, teamwork, and general success in learning English. It is suggested by the implications that gamification techniques be used to encourage learners' motivation, engagement, and positive social dynamics. Future studies could examine how gamification affects self-regulated learning mechanisms, intrinsic motivation, and language ability over the long run.